Use of life cycle assessment and eco-efficiency to evaluate alternative waste recovery: a study in the thermal power plant - Santos, Mario Roberto dos; Teixeira, Cláudia Echevenguá; Kniess, Cláudia Terezinha; Barbieri, José Carlos (Revista de Administração da UFSM, 2016)
The aim of this paper is to present a method to assess alternatives for waste recovery using combined mode the Life Cycle Assessment (LCA) and eco-efficiency measures. This method applied in relation to the bottom ash – waste from mineral coal combustion in thermal power plants – as an alternative raw material in place of industrial sand in the production of ceramic materials and the replacement of clinker used in the Portland cement production. The evaluation of eco-efficiency was performed according to the NBR ISO 14045 standard that guides the environmental impacts should be evaluated using LCA. The results showed that the eco-efficiency on the generation of bottom ash for use in the ceramic industry compared with the generation of bottom ash and disposal of thermal power plant in surface impoundment would increase from 0.2% down to 0.97% higher. Eco-efficiency on the generation of bottom ash for use in the cement industry compared with the generation of bottom ash and disposal of thermal power plant in surface impoundment would increase from 1% down to values between 2.4% and 11.5% higher. The application of the method showed that the use of bottom ash as a raw material of ceramic productions or clinker substitution of Portland cement productions improves the eco-efficiency of thermal power plants.